Prevalence of internet addiction among medical and non-medical students of international Islamic university Malaysia - Abdul Hadi, Azwanis; Azmi, Nurul Husna; Azmi, Fatin Nadrah; Jasmani, Norshahida; Mohd Salim, Fatin Salina; Abd. Aziz, Karimah Hanim (2021)
• Internet addiction has become a serious issue in today’s world especially among college students. • Studies have shown worrying prevalence of internet addiction, with most studies were done among medical students. • Only a few studies were carried out among non-medical students. • Griffiths MD, (2000) in his study stated that internet addiction can be linked to addictive disorders and grouped alongside alcohol and drug use disorders.